Cultural and Gender Variation in Argumentative Coherence: A Corpus-Based Study of Indonesian and Japanese EFL Learners - Bambang Ruby Sugiarto (JALL (Journal of Applied Linguistics and Literacy), 2026)
This study examines how cultural background and gender relate to argumentative coherence in English writing among Indonesian and Japanese EFL learners. Although intercultural rhetoric research has explored cross-cultural variation in argumentative structure, limited corpus-based studies have compared learners at controlled proficiency levels using a structured analytical framework. Drawing on 20 B1_2-level essays from the ICNALE corpus, this study applies the Toulmin Argument Pattern (TAP) framework to analyze the distribution of claims, data, counterclaims, and rebuttals. Argumentative quality was further assessed using an adapted coherence-level scale. The findings reveal clear cross-cultural variation: Indonesian learners produced a higher frequency of claims and supporting data, reflecting a predominantly linear argumentative structure, whereas Japanese learners more frequently incorporated counterclaims and rebuttals, resulting in more structurally complete argumentative cycles. Gender-related differences were observed in the distribution of argumentative elements; however, these patterns should be interpreted cautiously due to the exploratory sample size. Overall, the study highlights the role of culturally shaped rhetorical preferences in EFL argumentative writing and demonstrates the usefulness of TAP as a diagnostic tool for examining intercultural variation in coherence. Pedagogical implications and directions for future research are discussed.